Malaysian Corporation Analysis on Hedging Determinants and Performance - Zahid, Putra Faizurrahman; Zulqernain, Nurul Syaqirah; Ahmad, Noryati (Universiti Teknologi Mara Cawangan Kelantan, 2016)
This study is an empirical assessment on hedging determinants of non-financial corporations in Malaysia. The variables tested in the analysis are extracted from literature of hedging and derivative usage among corporations.The analysis considered 2566 public listed non-financial corporations across industries from the year 2006 to 2010, addressing the result of logistic regression on all samples (all corporations) and industry segregated by cross-sectional analysis using Eviews 7.0. It is found that liquidity, managerial risk aversion on option compensation, blockholder shares, firm market value and firm exposure are the factors for corporations to hedge. In industry segregated analysis, the firm market value is significant for all industries. Besides investigating the determinants of hedging issue, this study also examines the financial performance of corporation‟s hedging by using ROA and Tobin‟s Q performance indicator towards hedge and non-hedge corporations subsamples. It is found that hedger and non-hedger corporations have no significant difference in terms of financial performance, except at industry or sector level.It appears that Consumer Product‟s ROA, Industrial Product‟s ROA and Technology‟s ROA are significantly and positively related to hedging as predicted relationship. Plantation‟s Tobin‟s Q and Property‟s Tobin‟s Q also show significant positive relationship to corporations‟ hedging activities